Ceng-i İngilîs ve Osmânî der Beyne’n-Nehreyn (1913tâ 1918 m.) : Ve Avâkib-i an der İran = England against the Ottoman Empire : The War in Mesopotamia and its Repercussions in Iran, 1914-1918 A.D. - Abbâs Mîrza Ferman Fermayiyan (Salar-i Leşker), 1890-1935 (Tehran)
383 s.